Combined electromagnetic geophysical mapping at Arctic perennial saline springs: Possible applications for the detection of water in the shallow subsurface of Mars. Issue 9 (1st May 2017) - Samson, C.; Mah, J.; Haltigin, T.; Holladay, S.; Ralchenko, M.; Pollard, W.; Monteiro Santos, F.A.
Abstract: Perennial springs at the Gypsum Hill site on Axel Heiberg Island in the Canadian Arctic (79°24′N, 90°44′W) represent a high-fidelity analogue to hydrothermal systems that might exist on Mars. The springs were surveyed using an electromagnetic induction sounder (EMIS) and ground penetrating radar (GPR). Both instruments probed the subsurface to a depth of approximately 3 m. Lateral EMIS soundings were performed every metre along a 400 m long reconnaissance line roughly oriented SW-NE and extending through 23 active springs and 1 dry outlet to measure electrical conductivity. Two distinct zones were identified within the survey area on the basis of these data: in the southwest portion, sharp conductivity peaks correspond to isolated springs with well-defined outlets, flowing over dry rocky soil; in the northeast portion, the springs are fed by a pervasive network of saline fluids, resulting in high background readings and muddy surface conditions. These observations are consistent with vertical EMIS sounding data which showed that the brine body feeding the saline springs can be found closer to the ground surface towards the northeast portion of the survey site. In areas of high electrical conductivity, the GPR data exhibits strong scattering. The noisy areas are sharply defined and interpreted to correspond to narrow vertical conduits feeding individual spring outlets. The EMIS is a rugged instrument that could be included as payload in future rover-based Mars exploration missions aiming at probing the shallow subsurface for the presence of brine pockets.